2018
DOI: 10.1097/ajp.0000000000000617
|View full text |Cite
|
Sign up to set email alerts
|

Occupational and Ergonomic Factors Associated With Low Back Pain Among Car-patrol Police Officers

Abstract: Few occupational and ergonomic factors that police organizations could use to better tailor prevention were found to be associated with acute or subacute LBP and CLBP. This cross-sectional study is an efficient first investigation for screening hypotheses that should be confirmed in further cohort studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 50 publications
0
23
0
4
Order By: Relevance
“…LBP has multifactorial consequences in tactical populations. Current evidence has shown the importance of assessing psychosocial and physical function outcomes in tactical personnel [18,19]. Douma et al [18] found that police officers with chronic LBP had lower levels of quality of life in emotional and mental domains when compared to police officers without LBP.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…LBP has multifactorial consequences in tactical populations. Current evidence has shown the importance of assessing psychosocial and physical function outcomes in tactical personnel [18,19]. Douma et al [18] found that police officers with chronic LBP had lower levels of quality of life in emotional and mental domains when compared to police officers without LBP.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence has shown the importance of assessing psychosocial and physical function outcomes in tactical personnel [18,19]. Douma et al [18] found that police officers with chronic LBP had lower levels of quality of life in emotional and mental domains when compared to police officers without LBP. Due to the nature (stressful and dangerous) and the requirements (physical and mental) of the work of tactical personnel, LBP is highly likely to continue to be present in these professions, harming personnel, their agencies, and society in general.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations